2020
DOI: 10.3389/fvets.2020.00224
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thermographic Imaging in Canine Hindlimb Muscles After 6 Min of Walking—A Pilot Study

Abstract: Objective: To evaluate changes in superficial temperature of hindlimb muscles before and after a 6-min walk in healthy dogs. Methods: Two infrared thermographic images were captured of the proximal and distal hindlimbs of 11 healthy dogs before and after a 6-min walk. Orthopedic exam and objective gait analysis confirmed the healthy status of study subjects. Superficial temperatures of the gastrocnemius, biceps femoris, and gracilis were assessed. Analysis of images was performed using 2 different methods of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 42 publications
1
11
0
Order By: Relevance
“…Furthermore, we also compared the difference in the SI between the point and line ROI both before and after the 6MWT, but no significant results were found. Interestingly, previous research investigating the muscle temperature change of healthy dogs after a walking test using a similar ROI selection as the current study also found some different results (Repac et al 2020). Authors of this study demonstrated that the line ROI would be greater for early pathology detection as there were significant temperature increases in the muscles (e.g., biceps femoris) after walking when using the line ROI, rather than the point ROI.…”
Section: Discussionmentioning
confidence: 47%
See 3 more Smart Citations
“…Furthermore, we also compared the difference in the SI between the point and line ROI both before and after the 6MWT, but no significant results were found. Interestingly, previous research investigating the muscle temperature change of healthy dogs after a walking test using a similar ROI selection as the current study also found some different results (Repac et al 2020). Authors of this study demonstrated that the line ROI would be greater for early pathology detection as there were significant temperature increases in the muscles (e.g., biceps femoris) after walking when using the line ROI, rather than the point ROI.…”
Section: Discussionmentioning
confidence: 47%
“…Authors of this study demonstrated that the line ROI would be greater for early pathology detection as there were significant temperature increases in the muscles (e.g., biceps femoris) after walking when using the line ROI, rather than the point ROI. One explanation may contribute to the difference between the above-mentioned study and the current one -since we only investigated the temperature change of a cat's paw pad, the length of the line used in this study would be much shorter than the length Repac et al (2020). Consequently, the average temperature of the line ROI measured in this study may be more localised.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Infrared thermal imaging technology offers a method to indirectly investigate differential dog muscle activity after exercise on a simulated disaster rubble pile compared to treadmill exercise (10)(11)(12). It is hypothesized that the circulation, visualized by infrared thermal imagery, of dog muscles following treadmill exercise would be different than that following rubble search, due to the different movement patterns required for the two activities.…”
Section: Introductionmentioning
confidence: 99%